Comparison of nurses and hospitalized adolescents` perceptions about importance and observance of hospitalized adolescents` decision making - T Sadeghi; N Dehghan-Nayeri; R. Karimi (Iran University of Medical Sciences, 2011)
Background and Aim: Participating in decision making is an important patient's right observance of which by nurses is an essential need of hospitalized adolescents. The aim of this study was to assess and compare nurses and hospitalized adolescents` perceptions about the importance and observance of hospitalized adolescents` decision making.   Materials and Method: It was a cross sectional study, 175 nurses and 180 hospitalized ill adolescents who had inclusion criteria were selected by convenience sampling, The data were collected using two parallel self-completed questionnaires. Data were analyzed by SPSS software and using Mann-Whitney and Kruskal-Wallis tests.   Results: No statistically significant difference was found between nurses` and hospitalized ill adolescents` perceptions of importance and observance of hospitalized adolescents` decision making. In addition, the results showed that, from nurses' point of view, participation in care was the most important item, while adolescents believed that the presence of support person had the most importance. Both nurses and adolescents believed that the presence of support person was mostly observed.   Conclusion: According to the findings, from perception of two groups, hospitalized adolescents` decision making is important and moderately respected. Nurses can improve quality of care by recognotion and remove shackles of observance.